2017
DOI: 10.1161/circgenetics.117.001910
|View full text |Cite
|
Sign up to set email alerts
|

What Do We Really Think About Human Germline Genome Editing, and What Does It Mean for Medicine?

Abstract: Genome editing has captured widespread attention due to its potential therapeutic applications. Early studies with human embryos have established the feasibility of human germline genome editing but raise complex social, ethical, and legal questions. In light of the potential impact of genome editing on the practice of cardiovascular medicine, we surveyed ≈300 attendees at a recent American Heart Association conference to elicit their opinions on somatic and germline genome editing. The results were revealing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 6 publications
1
21
0
Order By: Relevance
“…Such a strategy is attractive in light of observations that less than half of patients adhered to statin therapy prescribed during the year following a myocardial infarction, even when provided at no cost to the patient (Choudhry et al, 2011), as well as the high costs of PCSK9 monoclonal antibodies that are taken every few weeks, for the lifetime, making it difficult for providers to obtain authorization from insurers for coverage of prescriptions. When physicians and scientists were polled about the gene-editing strategy, the majority were supportive and indicated they would take a therapy themselves (Musunuru et al, 2017).…”
Section: Lessons From Mendelian Randomizationmentioning
confidence: 99%
“…Such a strategy is attractive in light of observations that less than half of patients adhered to statin therapy prescribed during the year following a myocardial infarction, even when provided at no cost to the patient (Choudhry et al, 2011), as well as the high costs of PCSK9 monoclonal antibodies that are taken every few weeks, for the lifetime, making it difficult for providers to obtain authorization from insurers for coverage of prescriptions. When physicians and scientists were polled about the gene-editing strategy, the majority were supportive and indicated they would take a therapy themselves (Musunuru et al, 2017).…”
Section: Lessons From Mendelian Randomizationmentioning
confidence: 99%
“…Other scholars agree arguing, that “public sentiment has considerable influence over allocation of resources, political policy and participation rates in studies, all of which affect the course of research” (McCaughey et al, 2016, p. 571). More specific to gene editing, a survey of 301 attendees (74% basic scientists) at a plenary entitled “Scientific, Clinical and Ethical Implications of Genome Editing” at an American Heart Association conference in 2017 found that 72% indicated that they would not support “clinical applications of human germline genome editing if the public was not asked about their opinion on the issue” (Musunuru et al, 2017, p. 2). Lawyers and ethicists also advocate public engagement to prevent a potential backlash against media hype associated with germline editing obscuring or biasing the potential benefits gained from gene editing somatic cells within the clinic (Lanphier et al, 2015; Nicol et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A STAT-Harvard School of Public Health poll found that far more people trusted scientists and physicians to decide whether or not to allow changing the genes of unborn babies (53%) than government officials and policy makers (9%) [16]. A poll of several hundred scientists and physicians at a recent American Heart Association meeting found that there was broad support for adults using a genome-editing therapy to improve their health [17]. Indeed, 69% said they would opt to personally receive a safe, one-shot, genome-editing therapy that permanently reduced the risk of CHD.…”
Section: Germline Therapy?mentioning
confidence: 99%